Comparison of Shoulder Strength in Routinely Trained Badminton Players and Non-Badminton Players - Wong Zhen Feng; Hermawan Nagar Rasyid; Juliati Juliati (Faculty of Medicine Universitas Padjadjaran, 2017)
Background: Shoulder pain is a common reason for patients to seek medical help in any healthcare center. Shoulder pain is influenced by a few factors such as gender, posture during daily activities, aging and psychological factors. Based on the study of Epidemiology of Injuries and Prevention Strategies in Competitive Swimmers, shoulder pain due to shoulder injuries can be reduced by strengthening the shoulder muscle. Badminton has become one of the most popular sports in Asia, especially in Indonesia. This study was conducted to determine if badmintonis able to strengthen the shoulder muscle group. Methods: A cross-sectional analytic experimental study was conducted on September 2015 at Lodaya Badminton Training Center and Bale Padjadjaran of Universitas Padjadjaran. Subjects were 30 healthy male routinely trained badminton players and 30 non-badminton players who voluntarily follow the rstudy procedures. Strength measurement procedures were provided to the subjects after getting informed consent. Data analysis was performed using T-test.Results: The shoulder strength in routinely trained badminton players was significantly different from non-badminton players (P<0.05).Conclusions: Shoulder strength can be improved through routine training of badminton to reduce risk of shoulder injury. DOI: 10.15850/amj.v4n2.1083